Ayazpınar-Aşağıgülbahçe Fairy Chimneys: Geoheritage, Geosite and Geotourism Assets, Pertek (Tunceli), Eastern Türkiye - Sar, Abdullah; Rizeli, Mustafa Eren; Erturk, Mehmet Ali; Gungor, Yildirim (Springer Heidelberg, 2026)
In and around Pertek (Tunceli), located in the Southeastern Anatolian Orogenic Belt (Eastern, T & uuml;rkiye), a rich geodiversity comprising magmatic, volcanic, sedimentary, and metamorphic rocks from the Palaeozoic to the Quaternary is observed. One of the rich geodiversity is the Upper Miocene-aged Karabak & imath;r Formation, consisting of andesitic, basaltic, dacitic, and rhyolitic rock fragments and tuffs. The Karabak & imath;r Formation is located northwest of the Pertek district. Different ero-sion patterns resembling fairy chimneys are observed in the Karabak & imath;r Formation around the villages of Ayazp & imath;nar and A & scedil;a & gbreve;& imath;g & uuml;lbah & ccedil;e. The body lengths of fairy chimneys vary between 1 and 12 m, and the body diameters vary between 1 and 3 m. The caps at the top have an average diameter of 1-1.5 m and a thickness of approximately 1 m. This study aims to create geotourism routes by creating geological heritage inventories of these fairy chimneys, which are important for geotourism, and to create a sustainable development model for the area
Keywords: A & scedil;a & gbreve;& imath; G & uuml;lbah & ccedil;e; Ayazp & imath;nar; Fairy chimneys; Geological heritage; Geotourism